Evaluasi Kapasitas Saluran Drainase terhadap Debit Rencana di Kawasan Graha Raya, Kabupaten Tangerang - Debby Syafriyandi; Salsabila Septiansyah; Agum Abdadi; Muthia Raissa; Bernard Mayalfanda; Ilha Madonna; Ezra Andreas Saputra (Institut Teknologi Garut, 2026)
Rapid urban growth in the Graha Raya area, Tangerang, has created serious challenges for the drainage system. Drainage problems have become a crucial issue in rapidly developing urban areas such as Graha Raya, Tangerang Regency. Flooding and water ponding frequently occur due to the insufficient capacity of the existing drainage channels. This study aims to evaluate the adequacy of the existing drainage channel capacity against the design discharge as part of flood mitigation efforts. The research methodology includes the collection of hydrological and channel morphology data, calculation of runoff discharge using the Rational Method, and analysis of the hydraulic capacity of drainage channels by considering channel dimensions, slope, and roughness coefficients. The analysis results indicate that several major drainage channels in Graha Raya are unable to accommodate the design discharge under certain return periods. For the 25-year return period, with a rainfall value of 187 mm/day, the design discharge exceeds the channel capacity in several segments. Therefore, adjustments to the hydraulic dimensions are required to improve the performance of the drainage system and minimize the potential for flooding in the study area.